2011
DOI: 10.1111/j.1476-5381.2011.01207.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic treatment with a novel γ‐secretase modulator, JNJ‐40418677, inhibits amyloid plaque formation in a mouse model of Alzheimer's disease

Abstract: BACKGROUND AND PURPOSE γ‐Secretase modulators represent a promising therapeutic approach for Alzheimer's disease (AD) because they selectively decrease amyloid β 42 (Aβ42), a particularly neurotoxic Aβ species that accumulates in plaques in the brains of patients with AD. In the present study, we describe the in vitro and in vivo pharmacological properties of a potent novel γ‐secretase modulator, 2‐(S)‐(3,5‐bis(4‐(trifluoromethyl)phenyl)phenyl)‐4‐methylpentanoic acid (JNJ‐40418677). EXPERIMENTAL APPROACH The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 39 publications
(70 reference statements)
2
41
0
Order By: Relevance
“…We also showed that EVP-0015962 treatment of H4-APP 751 cells did not cause the accumulation of APP α- or β-CTFs at concentrations up to 10 μM, whereas the GSI LY-411,575 [16] led to their accumulation at a concentration as low as 1 nM (Figure 4B). Full length APP was not altered by treatment with either EVP-0015962 or LY-411,575, consistent with published findings [27,30,33,34]. …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…We also showed that EVP-0015962 treatment of H4-APP 751 cells did not cause the accumulation of APP α- or β-CTFs at concentrations up to 10 μM, whereas the GSI LY-411,575 [16] led to their accumulation at a concentration as low as 1 nM (Figure 4B). Full length APP was not altered by treatment with either EVP-0015962 or LY-411,575, consistent with published findings [27,30,33,34]. …”
Section: Resultssupporting
confidence: 91%
“…Chronic treatment of Tg2576 mice with other GSMs has demonstrated reductions in amyloid deposition [25-27]. Similarly, the histological analyses of the chronically treated Tg2576 mice demonstrated reductions in percent area and number of amyloid plaques in the neocortex and hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…The first GSM chemotypes were derived from NSAID carboxylic acids, with examples being EVP-0015962 5 which has completed phase II, as well as JNJ-40418677 6 and BIIB042. 7 Merck has developed piperidine carboxylic acids, such as GSM-1 8 and GSM-2, 9 which recently have been well-characterized.…”
mentioning
confidence: 99%
“…These compounds were important chemical tools that provided evidence that ␥-secretase could be modulated to reduce the more pathogenic A␤42 species, but that the in vitro potencies are weak (A␤42 IC 50 Ͼ 50 M) and brain penetration is limited. Several next generation NSAID-like GSMs with improved in vitro potency and brain penetration have recently been reported, including GSM-1, GSM-10h, and JNJ-40418677 (17)(18)(19). The non-NSAID-derived imidazole GSMs have a slightly different profile in that they lower the production of A␤42 and A␤40 while increasing the levels of A␤38 and A␤37 to differing degrees.…”
mentioning
confidence: 99%